S-based taxation under default risk - Paolo M. Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2005)
This article studies the characteristics of a S-based tax system under default risk. In particular we show that its neutrality properties depend on whether debt is protected or unprotected. In the former case, this system is neutral. In the latter case, where default timing is optimally chosen by shareholders, the S-based system is neutral with respect to real decisions only if the firm's and the lender's tax rate are equal. However, the shareholders? decision to default is always distorted.
Keywords: H32; H25; 330; capital structure; corporate taxation; neutrality; option pricing; Unternehmensbesteuerung; Duale Einkommensteuer; Zins; Steuerbegünstigung; Kreditrisiko; Theorie